Advances in Procedural Echocardiographic Imaging in Transcatheter Edge-to-Edge Repair for Mitral Regurgitation - Fan, Yiting; Chan, Jeffrey Shi Kai; Lee, Alex Pui-Wai (Frontiers in Cardiovascular Medicine, 2022)
Transcatheter edge-to-edge repair (TEER) therapy is recommended by the American College of Cardiology/American Heart Association (ACC/AHA) guidelines for selected patients with symptomatic severe or moderate-severe mitral regurgitation (MR). Echocardiography, in particular transesophageal echocardiography (TEE), plays a critical role in procedural planning and guidance for TEER. Recent innovations and advances in TEE techniques including three-dimensional (3D) imaging, unlimited x-plane imaging, live 3D multiplanar reconstruction, as well as transillumination imaging with color Doppler and transparency rendering have further enhanced procedural imaging for TEER, especially for complex diseases including commissural defects, clefts, and multi-segment pathologies. This review discusses the technology of these advanced procedural imaging techniques and provides a “step-by-step” guide on how to apply them during the TEER procedure with a focus on their added values in treatment of complex valve lesions.